Clinical application and feasibility of utilizing the PEDI-CAT to assess activity and participation among children receiving physical therapy incorporating hippotherapy. - Conroy, Susan; Evans, Trish; Butler-Moburg, Dana; Beuttler, Richard; Robinson, Janelle; Huebert, Matt; O Mahony, Erin; Grant-Beuttler, Marybeth (Physiotherapy Theory & Practice, 2023)
Hippotherapy (HPOT) is a physical therapy (PT) treatment tool using equine movement to improve mobility for children with movement impairments. Although research suggests HPOT improves body structure and function, there is limited evidence regarding its impact on activity and participation outcomes in a clinical setting. The Pediatric Evaluation of Disability Inventory Computer Adaptive Test (PEDI-CAT) may be useful in HPOT settings to highlight changes in activity and participation. 1) Evaluate the PEDI-CAT's sensitivity to changes in activity and participation among children receiving PT using HPOT; 2) determine feasibility of administering the PEDI-CAT in a HPOT setting; and 3) examine how PEDI-CAT scores influence clinical decision-making. Participants (N = 34) were children who attended weekly PT using HPOT for 6 months. The PEDI-CAT was completed for all participants by a parent or caregiver at initial treatment (T1) and 6 months later (T2). A linear mixed effects model was used to evaluate changes in scores over time. Team meetings occurred monthly to discuss how PEDI-CAT scores impacted treatment. There were significant improvements across 3 PEDI-CAT domains between T1 and T2 for all children with small effect sizes and nonsignificant changes noted within two diagnostic subgroups with small-to-medium effect sizes. The PEDI-CAT was completed by all participants without interrupting treatment flow. PEDI-CAT score reports enriched therapist-client conversations increasing shared decision-making. PTs who treat children using HPOT may feasibly use the PEDI-CAT to assess changes in activity level outcomes and to assist clinical decision-making.